Integrating Projek Penguatan Profil Pelajar Pancasila (P5) into the Merdeka Curriculum Tenth Graders’ Perception at SMA Gajah Mada - Restu Khoirina; Yanuar Dwi Prastyo (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This study explores the integration of the Pancasila Student Profile Strengthening Project (P5) into the Merdeka Curriculum, focusing on tenth graders at SMA Gajah Mada. Using qualitative methods, including questionnaires and interviews, the research examines students' perceptions of P5's implementation. Findings reveal that P5 effectively strengthens students' understanding of Pancasila values, encourages critical thinking, and fosters personal growth. More than 70% of respondents agreed that the program enhances their knowledge and ability to apply these values in real-life contexts. Teacher involvement, collaborative activities, and relevant learning materials were highlighted as key strengths, contributing to student engagement and satisfaction. However, some areas for improvement were identified, such as time allocation for activities and creating a more open environment for student expression. Overall, the P5 initiative is perceived as a valuable component of the Merdeka Curriculum, promoting holistic development and aligning education with national values and global challenges.